1q21.3 deletion involving GATAD2B: An emerging recurrent microdeletion syndrome. Issue 3 (17th February 2017) - Tim‐Aroon, Thipwimol; Jinawath, Natini; Thammachote, Weerin; Sinpitak, Praweena; Limrungsikul, Anchalee; Khongkhatithum, Chaiyos; Wattanasirichaigoon, Duangrurdee
Abstract : GATAD2B gene is involved in chromatin modification and transcription activity. Loss‐of‐function mutations of GATAD2B have recently been defined to cause a recognizable syndrome with intellectual disability (ID). Human TPM3 gene encoding thin filament protein is associated with myopathies. Both genes are located on chromosome 1q21.3. We herein report an infant with feeding difficulty, developmental delay, hypotonia, and dysmorphic features including small palpebral fissures, telecanthus, sparse hair and eyebrow, cup‐shaped ears, and clinodactyly. Karyotype was normal. Single nucleotide polymorphism array revealed a 1.06 Mb deletion of chromosome 1q21.3, which was confirmed to be de novo. The deleted region encompassed 35 genes, including three known disease‐associated genes, namely GATAD2B, TPM3, and HAX1 . We further identify and summarize seven additional patients with 1q21.3 microdeletion from literature review and clinical databases (DECIPHER, ISCA/ClinGen). Genomic location analysis of all eight patients revealed different breakpoints and no segmental duplication, indicating that non‐homologous end joining is a likely mechanism underlying this particular microdeletion. This data suggests that 1q21.3 microdeletion is a recurrent microdeletion syndrome with distinguishable phenotypes, and loss of function of GATAD2B is the major contributor of the characteristic facies and ID. Additionally, the deletion of TPM3 warrants a risk of concomitant muscle disease in our patient. © 2017 Wiley Periodicals, Inc.